HDAC6, A Novel Cargo for Autophagic Clearance of Stress Granules, Mediates the Repression of the Type I Interferon Response During Coxsackievirus A16 Infection - Zheng, Yingcheng; Zhu, Guoguo; Tang, Yinglian; Yan, Jun; Han, Song; Yin, Jun; Peng, Biwen; He, Xiaohua; Liu, Wanhong (Frontiers in Microbiology, 2020)
Autophagic cargoes ensure selective autophagy for the recognition and removal of various cytosolic aggregated proteins, damaged organelles, or pathogens. Stress granules (SGs), as antiviral immune complexes, serve a positive role in the type I interferon (IFN) response and can be targeted by autophagy (termed granulophagy). However, the cargo of granulophagy remains elusive, and it is still unknown whether granulophagy plays a role in viral infection. Here, we found that histone deacetylase 6 (HDAC6), a component of viral RNA-induced SGs, is a novel granulophagic cargo that is recognized by p62/Sequestosome 1 (SQSTM1) and mediates the degradation of SGs in coxsackievirus A16 (CA16)-infected cells. CA16 viral RNA activated the protein kinase RNA-activated (PKR)/eukaryotic translation initiation factor 2-alpha (eIF2α) pathway to promote SG assembly. The SGs were degraded by CA16-triggered autophagy via the interaction between the ubiquitin-associated (UBA) domain of p62 and the ubiquitin-binding domain (UBD) of HDAC6, which was bridged by a poly-ubiquitin chain. We also found that granulophagy repressed the type I interferon response and facilitated viral replication. These results suggest that HDAC6 might be the first identified granulophagic cargo and granulophagy could be a strategy that viruses apply to repress the antiviral immune response.